Identification and Analysis of Novel Inhibitors against NS3 Helicase and NS5B RNA-Dependent RNA Polymerase from Hepatitis C Virus 1b (Con1) - Yang, Na; Sun, Chaomin; Zhang, Lixin; Liu, Jianguo; Song, Fuhang (Frontiers in Microbiology, 2017)
Hepatitis C virus (HCV) leads to severe liver diseases, including liver fibrosis, cirrhosis and hepatocellular carcinoma. Nonstructural protein 3 helicase (NS3h) and nonstructural protein 5B RNA-dependent RNA polymerase (NS5B) are involved in the replication of HCV RNA genome, and have been proved to be excellent targets for discovery of direct-acting antivirals. In this study, two high-throughput screening systems, fluorescence polarization (FP)-based ssDNA binding assay and fluorescence intensity (FI)-based dsRNA formation assay, were constructed to identify candidate NS3h and NS5B inhibitors, respectively. A library of approximately 800 small molecules and crude extracts, derived from marine microorganisms or purchased from the National Compound Resource Center, China, were screened, with three hits selected for further study. Natural compound No.3A5, isolated from marine fungi, inhibited NS3h activity with an IC50 value of 2.8 μM. We further demonstrated that compound No.3A5 inhibited the abilities of NS3h to bind ssDNA in electrophoretic mobility shift assay and to hydrolyze ATP. The NS3h-inhibitory activity of compound No.3A5 was reversible in our dilution assay, which indicated there was no stable NS3h-No.3A5 complex formed. Additionally, compound No.3A5 exhibited no binding selectivity on NS3h or single strand binding protein of Escherichia coli. In NS5B assays, commercial compounds No.39 and No.94 previously reported as kinase inhibitors were found to disrupt dsRNA formation, and their IC50 values were 62.9 μM and 18.8 μM, respectively. These results highlight how identifying new uses for existing drugs is an effective method for discovering novel HCV inhibitors. To our knowledge, all inhibitors reported in this study were originally discovered with HCV anti-nonstructural protein activities in vitro.